2005
DOI: 10.1038/nmeth779
|View full text |Cite
|
Sign up to set email alerts
|

Real-time imaging of ligand-induced IKK activation in intact cells and in living mice

Abstract: The transcription factor NF-kappaB is a key regulator of cellular activation, proliferation and apoptosis. Defects in the NF-kappaB pathway contribute to a broad array of malignant, neurodegenerative and chronic inflammatory diseases. IKK-dependent IkappaB alpha degradation by the 26S proteasome is a critical NF-kappaB regulatory control point, which is emerging as an important target for drug development. To directly monitor regulation of IKK activation in intact organisms, we engineered an IkappaB alpha-fire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
144
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 29 publications
2
144
0
Order By: Relevance
“…The WT cDNA was then fused to codon-optimized firefly (Photinus pyralis) luciferase (FLuc) from the pGL-3 control plasmid (Promega) by using a strategy described in ref. 30. Construction of the pFLuc control plasmid is described in ref.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The WT cDNA was then fused to codon-optimized firefly (Photinus pyralis) luciferase (FLuc) from the pGL-3 control plasmid (Promega) by using a strategy described in ref. 30. Construction of the pFLuc control plasmid is described in ref.…”
Section: Methodsmentioning
confidence: 99%
“…Construction of the pFLuc control plasmid is described in ref. 30. In the final constructs, ␤-cat-FLuc and FLuc expression were driven by an immediate-early CMV promoter.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated that fusing ⌱B␣ to the firefly luciferase gene (⌱B␣-FLuc) enabled quantitative monitoring of ⌱B␣ degradation (which directly correlates with IKK activity) in vitro and in vivo (26). We then placed the fusion reporter under the control of an NF-B-responsive promoter (B 5 3 ⌱B␣-FLuc) and showed that it recapitulated the endogenous ⌱B␣ negative feedback loop (Fig.…”
mentioning
confidence: 99%
“…To image firefly luciferase, the media was changed to MEBSS containing 150 g/ml D-luciferin and images acquired with a Ͼ590 nm bandpass filter. Data analysis was performed as described (29,30).…”
Section: Generation Of Recombinantmentioning
confidence: 99%
“…Animal care and euthanasia were approved by the Washington University Medical School Animal Studies Committee. Bioluminescence imaging was performed on the IVIS under 2.5% isoflurane anesthesia at the indicated time points as described (29,30). After imaging, animals were killed by cervical dislocation.…”
Section: Generation Of Recombinantmentioning
confidence: 99%